Про механізм хемосорбції і дисоціації хемосорбованих молекул кисню на окисах - Пенюх, Б.; Іванків, Л. (Праці наукового товариства ім. Шевченка, 2011)
The paper is devoted to the study of the kinetics of chemosorption and its mechanisms. The results of comprehensive experimental studies of the inter action of oxygen with oxides as well as the interpretation of the measurements data are presented. The interaction of O₂ with oxides at certain conditions is accompanied by the growth of the work function of exit by the change of adsorbent conductivity by heating up its surface by dissociation of chemosorpted molecule and by the emission of photons by adsorbent. The kinetics of these phenomena has been studied. From the mass law there has been obtained an equation of the speed of chemosorption which yields ( in graphic form) phenomenological formulas of Benhem and Yelovich, the interrelation between them as well as the distribution of adsorption centers by energy activation.